Population structure of free-ranging introduced monk parakeets (Myiopsitta monachus) in Santiago, Chile - Sandoval-Rodriguez, Alejandra; Barria, Agustin; Mendez, Marco A.; Larraechea, Matilde; Cristobal, Briceno (My University, 2024)
The monk parakeet (Myiopsitta monachus) is an invasive species introduced in Chile during the early seventies and now abundant in several areas of Santiago metropolis. For most of our knowledge, there are no genetic studies focused on the invasion of monk parakeets in Chile. The current study aims to assess the levels of population structure in monk parakeets from different municipalities in Santiago through next generation sequencing. Genetic material was obtained from pectoral muscle collected from monk parakeet fledglings (n = 204) sampled in Santiago, Chile. Using Double digest, restriction-site associated DNA (ddRADseq), 102,834 loci and 3195 SNPs were identified, allowing a high-resolution study in a population with little genetic diversity explained by an invasive founder effect. Genetic structure was modeled using the fixation index, STRUCTURE, and principal component analyses. Results showed low levels of genetic structure in the monk parakeet population from Santiago, evidencing high genetic flow between all studied municipalities. However, slight differences were observed when parakeets from the northern areas of Santiago were compared to those from the rest of the city. The geography of the city might explain these differences; with a small succession of hills of up to 400 m, potentially in-part isolating a northern reproductive colony. It is also possible that this northern population originated from or bred with a different release event or a combination of these factors. This study represents the first genetic characterization of monk parakeets in Chile and provides a high-resolution model to study recent invasion processes.
Keywords: ddradseq; invasive species; genetic structure; myiopsitta monachus; monk parakeet; quaker parrot